Performance and user acceptance of the Bhutan febrile and malaria information system: report from a pilot study. (December 2016) - Tobgay, Tashi; Samdrup, Pema; Jamtsho, Thinley; Mannion, Kylie; Ortega, Leonard; Khamsiriwatchara, Amnat; Price, Ric; Thriemer, Kamala; Kaewkungwal, Jaranit
Abstract Background Over the last decade, Bhutan has made substantial progress in controlling malaria. The country is now in an elimination phase, aiming to achieve no locally transmitted malaria by 2018. However, challenges remain and innovative control strategies are needed to overcome these. The evaluation and user acceptance of a robust surveillance tool applicable for informing malaria elimination activities is reported here. Methods The Bhutan Febrile and Malaria Information System (BFMIS) is a combination of web-based and mobile technology that captures malariometric surveillance data and generates real time reports. The system was rolled out at six sites and data uploaded regularly for analysis. Data completeness, accuracy and data turnaround time were accessed by comparison to traditional paper based surveillance records. User acceptance and willingness for further roll out was assessed using qualitative and quantitative data. Results Data completeness was nearly 10 % higher using the electronic system than the paper logs, and accuracy and validity of both approaches was comparable (up to 0.05 % in valid data and up to 3.06 % inaccurate data). Data turnaround time was faster using the BFMIS. General user satisfaction with the BFMIS was high, with high willingness of health facilities to adopt the system. Qualitative interviews revealed several areas for improvement before scale up. Conclusions The BFMIS had numerous advantages over the paper-based system and based on the findings of the survey the Vector-Borne Disease Control Programme has taken the decision to incorporate the BMFIS and expand its use throughout all areas at risk for malaria as a key surveillance tool.